Treatment seeking behavior of filariasis patients in a selected endemic area of Bangladesh - Rahman, KMM; Laskar, MS; Basu, BK; Chowdhury, S (Mediscope, 2015)
This descriptive cross-sectional study was carried out among 400 respondents from the rural area in Parbatipur Upazilla under Dinajpur district with the objectives to assess the knowledge, attitude, practice and gender discrimination of filariasis patients using a semi structured questionnaire through face to face interview. After collection of data, they were checked, verified, edited for consistency and entered into a computer. The statistical calculation and analysis were done to fulfill the objectives of the study. All the respondents were adult, age ranged from 20 to 71 years; mean (SD) was 41.3 (11.6). Among them 59.0% were female and 41.0% were male, about 90.5% were married, 68.5% were illiterate and 4.0% had higher secondary education. About 78.5% of the respondents in the studied area had no knowledge about the disease. All the respondents had incorrect concept about the causes of the disease. About 85% of the respondents mentioned that the symptoms of the disease was swelling of the hand and feet, 12.6% reported no specific symptoms or had no knowledge on symptoms of the disease; 67.8% of the men reported swelling of the scrotum. About 94% of the respondents did not know the easiest method of prevention. About 73.8% of the respondents delayed in receiving the treatment and 26.3% received treatment immediately after appeared of symptoms. About 51.5% respondents did not take the disease seriously and 48.5% did not receive advice from any one. From the respondents, 89.5% received treatment from homeopaths, 83.5% from kabiraj, and 7.8% from doctors with MBBS (from private clinics) and 0.3% from government hospitals. Analysis revealed that female respondents received different pattern of treatment than male counterpart. Active community participation should be ensured in designing community based education campaigns to make them socially acceptable and effective. Health workers, NGO workers, teachers, religious leaders, community leaders can play a key role convincing the patients to take modern treatment and enhancing the intake of full course of drugs against filariasis by the patients. Further study is needed using a large scale patients to observe the actual status of treatment seeking behavior of filariasis patients in the community. Mediscope Vol. 2, No. 2: July 2015, Pages 5-15